Improve the long jump student through attitude responsibility and use two models - Kastrena, Ervan; Eka Nugraha, Adang Suherman, Amung Ma’mun, (Opción, 2019)
The aim of this study is to examine the effectiveness of the personalized system of instruction (PSI) learning model compared to the direct instruction learning model (DI) via an experimental method with a 2x2 factorial design. The results revealed that long jump learning with PSI was better than DI, then students with a high level of responsibility reveal that they are more suitable to do learning with PSI while students with a low responsibility attitude experience increased long jump skills through DI. In conclusion, the PSI learning model can be an effective way to improve squat style long jump skills